Hemileccinum pruinatus (Boletaceae, Boletales), a new bolete from subtropical China - Zhao, Run-Xiang; Zhong, Qiao-Wen; Ke, Bin-Rong; Zeng, Zhi-Heng; Zeng, Hui; Zeng, Nian-Kai (Phytotaxa, 2025)
Hemileccinum pruinatus (Boletaceae, Boletales) from Fujian, subtropical China, is described as new based on morphological and phylogenetic evidence. An illustrated morphological description as well as comparisons with related species are presented. Additionally, a key to the accepted species of Hemileccinum in China is provided.